The Mediating Role of Person–Job Fit in the Relationship Between Job Crafting and Innovative Work Behavior: A Study on Five-Star Hotels - Kaya, İrem Kılıç and Bulgurcu Gürel, Esra Burcu (International Review of Management and Marketing, 2026)
Increasingly intense competitive conditions in today’s world have made innovative work behavior (IWB) a strategic necessity and a behavior expected by organizations. Within this context, the present study examines whether person–job fit (PJF) operates as a mediating mechanism in the relationship between job crafting and innovative work behavior (IWB). The study population comprises employees working in five-star hotel establishments in Muğla, Türkiye, and the empirical analysis is based on data collected from 353 employees. Structural equation modeling (AMOS-SEM) was employed to test the relationships among the study variables. The findings indicate that the task, cognitive, and relational dimensions of job crafting are all positively and significantly associated with IWB. The mediation analysis results reveal that PJF plays a mediating role in the effects of the cognitive and relational dimensions of job crafting on IWB, whereas no significant mediation effect was detected for the task dimension. These findings suggest that promoting innovative behavior in hotel establishments may depend not only on employees’ task-related activities but also on how they interpret their work and manage their workplace relationships.